Evaluation of Anti-Diarrheal Activity of Methanol Root Bark Extract of Milicia Excelsa (Welw) C. C Berg (Moraceae) in Rats - Adebayo, Muritala Ayofe; Adedokun, Oluwasegun Adekanmi; Akinpelu, Lateef Abiola; Okafor, Paul Okwudili (Drug Research, 2019)
Milicia excelsa (Moraceae) plant is used as an antidiarrheal agent in ethnomedicine but there is no scientific rationale for its claim. Hence, this study examined the acute toxicity (LD50) and anti-diarrheal effect of methanol root bark extract of Milicia excelsa per oral in rats as well as the probable phytoconstituents responsible for this effect. The LD50 was>5000 mg/kg, suggesting its safety. The extract significantly (p<0.05) reduced the total number of feces and wet feces in castor oil-induced diarrhea with percentage inhibitions of 41.36 and 50.88% at 200 and 400 mg/kg respectively; it also significantly (p<0.05) reduced the distance travelled by charcoal in a dose dependent manner with percentage inhibitions of 33.85, 43.07 and 50.76% at 100, 200 and 400 mg/kg respectively in gastrointestinal motility test indicating anti-diarrheal potentials. The extract significantly (p<0.05) reduced the intestinal fluid accumulation with percentage inhibitions of 33.28 and 45.61% at 200 and 400 mg/kg respectively, suggesting antisecretory effect. Furthermore, the extract significantly (p<0.05) inhibited the intestinal propulsion of the charcoal meal through the gastrointestinal tract in castor oil-induced gastrointestinal transit suggesting antimotility effect. Total flavonoids and tannins are the most abundant phytoconstituents therein. This study therefore concluded that the anti-diarrhea action of the extract may at least in part be mediated via antisecretory and antimotility mechanisms, which could be due to the additive, synergy or counter interaction of the phytoconstituents therein, thus supporting its ethnomedicinal claim.
Keywords: Milicia excelsa; castor oil-induced diarrhea; gastrointestinal motility; toxicity; phytoconstituents